2017
DOI: 10.1108/mbr-07-2017-0050
|View full text |Cite
|
Sign up to set email alerts
|

Different role of lobbying and bribery on the firm performance in emerging markets

Abstract: Purpose Firms influence a government to their advantage in one of two ways: either through lobbying a government to change the rule, or through bribing bureaucrats to circumvent the rule. The purpose of this paper is to investigate whether and under what conditions do corporate political activities facilitate firm growth in a multinational context, especially in developing economies. Design/methodology/approach This study is based on the data of the World Bank’s Enterprise Survey, conducted by the World Bank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 75 publications
(81 reference statements)
1
22
0
Order By: Relevance
“…Bribery can be a fee (Grzywacz et al 2004) that firms pay to avoid hassles, disadvantages, or unfair treatment. Furthermore, bribery can exist in a passive form, not to gain exclusive benefits, but rather to break even (Yim et al 2017).…”
Section: Bribery and Corruptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bribery can be a fee (Grzywacz et al 2004) that firms pay to avoid hassles, disadvantages, or unfair treatment. Furthermore, bribery can exist in a passive form, not to gain exclusive benefits, but rather to break even (Yim et al 2017).…”
Section: Bribery and Corruptionmentioning
confidence: 99%
“…In emerging markets, the bargaining power of government officials can be powerful as they seek private gain from their relationship with firms (Lee et al 2010). The pervasiveness of country-level corruption and level of institutional development both influence the act of bribery (Yim et al 2017). Martin et al (2007) found that the bribery activities of local firms are affected by various cultural values and institutional characteristics.…”
Section: Bribery and Corruptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another perspective on this adverse consequence is related with the political CSR. Fooks, Gilmore, and Collin [28] and Cai, Jo, and Pan [29] examine the controversial industry, such as tobacco and gambling industry, and argue that firms in these industries conduct CSR only to neutralize the forced policy and regulatory pressure. In 2018, Lee Jae-yong, the vice president of Samsung and only son of South Korean electronics giant has been jailed for five years as part of a whopping corruption scandal that also prompted the impeachment of the Korean former President Park Geun-hye.…”
Section: Hypothesis Developmentmentioning
confidence: 99%